The effect of employment stress on employment anxiety among physical education students: the mediating role of social support and psychological resilience - Wang, Jie; Zhang, Ruohan (Frontiers in Psychology, 2025)
ObjectiveThis study aims to investigate the relationship between employment stress and employment anxiety in physical education students, especially the mediating role of social support and psychological resilience.MethodsGroup psychological measurements were administered to 532 students using the Employment Stress Scale for College Students, Social Support Rating Scale (SSRS), Brief Resilience Scale (BRS), and the Questionnaire for Suppression of Career Anxiety in College Graduates, in which the data were analyzed using SPSS 26.0 and the Bootstrap method to analyze the data, test and analyze the effects.ResultsEmployment stress was positively related to employment anxiety, and employment stress can significantly be used to predict employment anxiety in physical education students. In addition, employment stress can play a negatively predicted role in social support and psychological resilience, in turn, both factors can also have a negative prediction role on employment anxiety at the same time. Social support and psychological resilience were identified as significant mediators between employment stress and employment anxiety with three mediating pathways: employment stress, social support and employment anxiety (Path 1), with an indirect effect of 0.122 and Bootstrap 95% confidence intervals excluding 0 (LLCI = 0.099, ULCI = 0.144), accounted for 15.20% of the total effect. Employment stress, psychological resilience, and employment anxiety (Path 2), with an indirect effect of 0.064 and Bootstrap 95% confidence intervals excluding 0 (LLCI = 0.016, ULCI = 0.115), accounting for 8.00% of the total effect. Employment Stress, Social Support, psychological resilience, employment anxiety (Path 3), with an indirect effect of 0.006 and Bootstrap 95% confidence intervals excluding 0 (LLCI = 0.002, ULCI = 0.011), accounts for 0.70% of the total effect.ConclusionEmployment stress has positively predictive effects on employment anxiety in physical education students and has a ripple effect on anxiety symptoms in physical education students through the mediating role of social support and psychological resilience. The research results show that providing social support and increasing psychological resilience can effectively improve the individual’s coping level, alleviate the impact of employment stress, and thus reduce employment anxiety, which will be beneficial to the physical and mental health development of physical education students. At the same time, it provides a theoretical basis for graduate employment guidance and employment psychology education, and better helps physical education students make career choices.